Improving crop growth by enhancing 5-aminolevulinic acid production by plant-growth-promoting-bacteria - Farah, Farah (2020)
There is an increasing need to produce crops sustainably and one way of doing that is to use plant growth promoters and/or natural products which will encourage crop growth whilst maintaining soil health. A nonprotein amino acid called 5-aminolevulinic acid (ALA) has been shown to enhance plant growth when used at low concentrations, although it causes oxidative stress at high doses. ALA is used in medicine and in food production and whilst ALA can be synthesised chemically, the expense of doing so is driving research into developing microbial production systems primarily utilising photosynthetic bacteria. Prior to the start of this project, an unidentified bacterium which demonstrated plant (rice) growth promoting ability that was thought to be due to natural production of ALA, was isolated from a peat soil. The aims of the current study were to test the potential of this bacterial isolate to promote plant growth and to evaluate the consequences of applying ALA to three contrasting brassica species. The bacterium was identified as Bacillus paramycoides following 16S sequencing and a series of bacterial growth experiments were conducted to measure ALA production as a function of cell number (expressed as optical density at 600 nm). There was a close relationship between ALA concentration in the growth medium and OD600. ALA production by Bacillus paramycoides was optimised in a further set of experiments during which glutamate and levulinic acid (a reaction precursor and an inhibitor of ALA dehydratase respectively) were utilised. The maximum ALA concentration measured was around 200 µM which is in line with published concentrations. Following confirmation that the bacterium produced ALA, the bacterial culture medium containing metabolites was used to moisten filter papers on which cress (Lepidium sativum) seeds were sown. Presence of metabolites only increased germination and seedling biomass relative to metabolite-free medium when highly diluted. No effect of the bacterial metabolites on growth of kale (Brassica oleracea var. acephala) in peat-based soil was observed, although kale responded positively to a low concentration (0.0012 mM) of ALA applied as a seed dressing and negatively to a higher concentration (0.12 mM). Radish was less responsive to ALA than either cress or kale. Overall, the plant response to ALA amendment was species and dose-dependent, with low ALA concentrations generally initiating a positive response, whilst high concentrations were often deleterious. FTIR spectra for plants subjected to a seed soaking ALA treatment before sowing, or to a foliar spray at the 3-4 true leaf stage, presented differently from one another. Spectra for seed-treated plants appeared to be indicative of a stronger biochemical response to higher concentrations of ALA than plants given the foliar spray instead. Seedling/plant sensitivity and stage of growth should therefore be considered when treating plants with ALA. The findings here corroborate the general view that ALA benefits plants at a low concentration, but, is phytotoxic at high doses. However, the data also suggest that the ALA response is species specific and varies with application method as well as being dose dependent. The spectra highlight that ALA may cause damage to plants which is not overtly evident because it may not translate into altered biomass.